Impact of Minimal Residual Disease on Progression-Free Survival Outcomes After Fixed-Duration Ibrutinib-Venetoclax Versus Chlorambucil-Obinutuzumab in the GLOW Study - Munir, Talha; Moreno, Carol; Owen, Carolyn; Follows, George; Benjamini, Ohad; Janssens, Ann; Levin, Mark-David; Osterborg, Anders; Robak, Tadeusz; Simkovic, Martin; Stevens, Don; Voloshin, Sergey; et al. (Journal of clinical oncology, 2023)
PURPOSE: In GLOW, fixed-duration ibrutinib + venetoclax showed superior progression-free survival (PFS) versus chlorambucil + obinutuzumab in older/comorbid patients with previously untreated chronic lymphocytic leukemia (CLL). The current analysis describes minimal residual disease (MRD) kinetics and any potential predictive value for PFS, as it has not yet been evaluated for ibrutinib + venetoclax treatment. METHODS: Undetectable MRD (uMRD) was assessed by next-generation sequencing at <1 CLL cell per 10,000 (<10-4) and <1 CLL cell per 100,000 (<10-5) leukocytes. PFS was analyzed by MRD status at 3 months after treatment (EOT+3). RESULTS: Ibrutinib + venetoclax achieved deeper uMRD (<10-5) rates in bone marrow (BM) and peripheral blood (PB), respectively, in 40.6% and 43.4% of patients at EOT+3 versus 7.6% and 18.1% of patients receiving chlorambucil + obinutuzumab. Of these patients, uMRD (<10-5) in PB was sustained during the first year post-treatment (EOT+12) in 80.4% of patients receiving ibrutinib + venetoclax and 26.3% receiving chlorambucil + obinutuzumab. Patients with detectable MRD (dMRD; ≥10-4) in PB at EOT+3 were more likely to sustain MRD levels through EOT+12 with ibrutinib + venetoclax versus chlorambucil + obinutuzumab. PFS rates at EOT+12 were high among patients treated with ibrutinib + venetoclax regardless of MRD status at EOT+3: 96.3% and 93.3% in patients with uMRD (<10-4) and dMRD (≥10-4) in BM, respectively, versus 83.3% and 58.7% for patients receiving chlorambucil + obinutuzumab. PFS rates at EOT+12 also remained high in patients with unmutated immunoglobulin heavy-chain variable region (IGHV) receiving ibrutinib + venetoclax, independent of MRD status in BM. CONCLUSION: Molecular and clinical relapses were less frequent during the first year post-treatment with ibrutinib + venetoclax versus chlorambucil + obinutuzumab regardless of MRD status at EOT+3 and IGHV status. Even for patients not achieving uMRD (<10-4), PFS rates remained high with ibrutinib + venetoclax; this is a novel finding and requires additional follow-up to confirm its persistence over time.
Keywords: doba přežití bez progrese choroby; bicyklické sloučeniny heterocyklické; Neoplasm, Residual; protokoly protinádorové kombinované chemoterapie; Leukemia, Lymphocytic, Chronic, B-Cell; lidé; Chlorambucil; senioři; Bridged Bicyclo Compounds, Heterocyclic; chlorambucil; Aged; reziduální nádor; Progression-Free Survival; chronická lymfatická leukemie; Antineoplastic Combined Chemotherapy Protocols; Humans